Persepsi Terhadap Kekerasan Domestik Berdasarkan Sudut Pandang Religiusitas dan Peran Sosial - Susilo, Markus Nanang Irawan Budi; Kurniawan, Yudi; Amelia, Cristine Roselvia Tri (Jurnal Riptek, 2024)
The city of Semarang is a city that is increasingly developing and is pursuing policies to become a decent, safe and livable city. However, cases of violence still occur and have even increased. The efforts made are to provide education and assistance to the community, with the hope of providing understanding and improving morals. The existence of the situation, the efforts of the City of Semarang to create a safe situation but it turns out that it still occurs and even the number of cases of domestic violence has increased, raising the question of how society perceives violence. When it is shown that most of the perpetrators are those closest to them, even their own parents, another question arises, namely whether society, especially, has learned and understood their social roles in the family, whether as father, mother, wife, husband, and/or other social roles. Coupled with the condition as an adult human being which should also be increasingly mature in terms of religiosity, this also raises the question of whether religiosity still has an influence on perceptions of domestic violence. The results of the research analysis show that the magnitude of the relationship between Religiosity and Social Roles and Perceptions of Domestic Violence has a correlation coefficient value of 0.542 with a sig value = 0.000, meaning that there is a very significant relationship between Religiosity and Social Roles and Perceptions of Domestic Violence so that the hypothesis is accepted. Meanwhile, the simultaneous contribution of Religiosity and Social Role to Perceptions of Domestic Violence is 29.4% and 70.6% determined by other variables